The Philippines' and Singapore's journeys towards liberalised electricity supply industries - Takeaways for Malaysia - Aris H.; Mohd Zawawi I.S.; Jrgensen B.N. (MDPI AG, 2023)
Computer science; Energy management; Best practices; Course of action; Good practices; Implementation phasis; Legislative frameworks; Philippines; Renewable energy penetrations; Southeast Asia; Energy policy